Representation of Cultural Conflict in Fictionalizing Pre-Revolutionary Era in China: An Analytical Study of the Novel the Good Earth of Pearl S Buck: Exploring Cultural Conflicts in Pre-Revolutionary China: An Analysis of Pearl S. Buck's The Good Earth (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Good Earth, a novel by Pearl. S. Buck, portrays the true picture of China during the rule of the last royal family. The novelist is the daughter of missionaries staying in China who are well acquainted with Chinese life in the village. The novel was published at the beginning of the 20th century, a period of turmoil in Chinese history. During the phase covered by the book, China experienced major political shifts. The global and social upheavals of the 20th century is nothing but a remote echo of average people's lives. This novel gives readers a near glimpse into China's inner existence and its inhabitants. The book that talks about the family, beliefs, strategy and custom of the Chinese people helped to keep China friendly after the First World War. This paper tries to examine the seriousness of the adjustments that occurred in China throughout the pre-Revolutionary period.